UMK Global Chairman Lecture Series 16/2013 (GCLS 16) - Universiti Malaysia Kelantan, Canselori (2013)
18th May 2013: Universiti Malaysia Kelantan organizing UMK Global Chairman Lecture Series 16/2013 (GCLS 16). The theme of the lecture is : "ENTREPRENEURSHIP & RISK MANAGEMENT". Welcoming remarks by YBhg. Prof. Dr. Nik Maheran Nik Muhammad (Professor of Finance, UMK) & Chairman Lectures (Speaker 1) by : YBhg. Dato' Dr. Sr. Kamarul Rashdan Hj. Salleh (Managing Director, SPNB).